Kebijakan Kepala Sekolah dalam Meningkatkan Mutu Melalui Manajemen Peserta Didik - Utami, Indah Hari; Nasution, Umaruddin (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2020)
This study examines the management of learners at MI Ma'arif Bego. The focus of the discussion on this research is how the school's policy on the management of students at MI Ma'arif Bego aims to find out how the student admissions process at MI Ma'arif Bego, how the development of interest Talents of the students at MI Ma'arif Bego and how the results and evaluation learnt students at the Mi ma'arif Bego. The study used a qualitative approach with field study methods and data collection techniques through principal interviews and documentation. The results of this study show that the principal's policy on student management is 1) Student acceptance Policy 2) development of students ' interests and talents and 3) Evaluation of learners ' learning outcomesKeywords: management, learners.